Spin-dependent rescattering in strong-field ionization of helium. (28th February 2017) - Zille, D; Seipt, D; Möller, M; Fritzsche, S; Gräfe, S; Müller, C; Paulus, G G
Abstract: We investigate the influence of singlet and triplet spin states on rescattered photoelectrons in strong-field ionization of excited helium. Choosing either a symmetric or antisymmetric spatial wave function as the initial state results in different scattering cross sections for the 1 s 2 s 1 S and 3 S states. These cross sections are used in the semi-classical model of strong-field ionization. Our investigations show that the photoelectron momentum distributions of rescattered electrons exhibit a significant dependence on the relative spin state of the projectile and the bound electron which should be observable in experiments. The proposed experimental approach can be understood as a testbed for probing the spin dynamics of electrons during strong-field ionization and the presented results as a baseline for their identification.